Probiotic in Quail Nutrition: A Review - Vali, Nasrollah (International Journal of Poultry Science, 2009)
The digestive tract must supply the factors necessary for the existence of any micro-organism that finally becomes established. These factors include a favorable temperature, a constant supply of nutrients and essential fluids: In this situation the micro-organisms benefit from the environment and the animal benefits by maintaining a microflora that does not cause any disease state. There are generally two different types of bacterial populations which can become established in the digestive tract. The first is that which exists in close association with the gut epithelium and the second is that which occurs free in the gut lumen. The ideal situation throughout the life of any animal would be to maintain specific numbers of beneficial bacteria in the digestive tract. This would ensure that at all times the animal would have the proper microbial balance. The term “probiotic ” has been used to indicate substances or micro-organisms which contribute to an ideal microbial balance. Today probiotics are considered as those viable microorganisms that when administered to man and animal, beneficially affects the host by improving the properties of the indigenous microflora. To maintain the intestinal microflora balance in animals it is important to prevent diseases by controlling the overgrowth of potentially pathogenic bacteria. Although known since a long time, only in the last two decades probiotics have started to receive major attention from researchers, and several studies have been carried out on the effects of probiotics microorganisms, using different formulae and with numerous purposes of preventing or treating diseases.